A RELATIONSHIP BETWEEN OWNER-MANAGER’S CHARACTERISTIC AND BUSINESS PERFORMANCE - Nimalathasan, B. (My University, 2008)
Effective and efficient use of resources ultimately determines the overall performance of the organization. In this way performance of the organization depends on how the management of the organization drafting their strategies and implement practices for all organization to handle the resources in effective and efficient manner. These practices are determined by the entrepreneurial characteristics. Entrepreneur to Entrepreneur, the characteristic vary and their practices also vary. It is therefore important to understand the relationships between the entrepreneurial characteristics and organizational performance. This paper will help to understand to what extent the entrepreneurial characteristic can go to determine the Business performance. Even though there is number of views and ideas broadening the concepts of managing business successfully. Therefore this study will contribute to enrich the knowledge in the field to somewhat extent. Thus the paper is focused to analyze the “Relationship between owner-manger’s characteristics and business performance. Cooper (1998) that there is an empirical relationship between the business founding processes of entrepreneurs and the performance of their businesses. The result also support kotey’s and Meredith’s (1997) broad finding that the personal values of owner /managers, the strategies they adopt in operating their firms, and the performance outcomes of their businesses are empirically related. Based on the empirical research, there is positive relationship between owner manger’s characteristics and Business Performance.